2015
DOI: 10.1186/s12940-015-0004-0
|View full text |Cite
|
Sign up to set email alerts
|

A nested case-control study indicating heavy metal residues in meconium associate with maternal gestational diabetes mellitus risk

Abstract: BackgroundEnvironmental pollutant exposure may play certain roles in the pathogenesis and progression of diabetes mellitus including gestational diabetes mellitus (GDM). We hypothesize that heavy metal exposure may trigger GDM during pregnancy. The objective of this study was to investigate the possible associations between selected heavy metal exposure and GDM risk.MethodsThis investigation is a retrospective case–control study nested within a cohort of 1359 pregnant women. These participants were recruited i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 55 publications
(82 reference statements)
2
50
2
Order By: Relevance
“…Two previous studies, a U.S. based cohort study (Ettinger et al, 2009) and a Chinese case-control study (Peng et al, 2015), both found significant associations between arsenic exposure and gestational diabetes. Other studies have examined arsenic exposure in relation to type 2 diabetes.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Two previous studies, a U.S. based cohort study (Ettinger et al, 2009) and a Chinese case-control study (Peng et al, 2015), both found significant associations between arsenic exposure and gestational diabetes. Other studies have examined arsenic exposure in relation to type 2 diabetes.…”
Section: Discussionmentioning
confidence: 92%
“…The third and fourth quartiles of cadmium exposure were associated with a significantly increased risk of gestational diabetes. Interestingly, they found significantly reduced odds ratios for the second and third quartile of lead compared to the first quartile (Peng et al, 2015).…”
Section: Figmentioning
confidence: 92%
“…A nested case–control study within pregnancy cohort of Chinese women compared metals, including As, in meconium samples from infants born to healthy mothers ( n  = 190) or mothers with GDM ( n  = 137). Meconium As was dose-dependently associated with maternal GDM (OR: 3.3, 95 % CI: 1.2, 8.7; OR: 3.4, 95 % CI: 1.3, 8.8; and OR: 5.3, 95 % CI: 2.0, 13.9, for the 2nd, 3rd and 4th quartiles of meconium As, respectively) [23]. …”
Section: Discussionmentioning
confidence: 99%
“…Although few epidemiological studies have examined As exposure and GDM, data are beginning to emerge on the potential role for As in the development of impaired gestational glucose control [2123]. Specifically, only three prior studies have examined the association between As and GDM, and of these, two were limited in that they relied solely on postpartum As exposure assessments.…”
Section: Introductionmentioning
confidence: 99%
“…Exposures to persistent organic pollutants (POPs), such as organochlorine compounds (OCs) and perfluoroalkyl substances (PFASs), and exposures to metals, such as mercury, have been associated with increased risk for type 2 diabetes (reviewed in Lee et al 2014; Kuo et al 2013; Magliano et al 2014; Taylor et al 2013). However, only a few previous studies, with inconclusive findings, have specifically focused on risk of GDM (Jaacks et al 2016; Peng et al 2015; Shapiro et al 2015 and 2016; Smarr et al 2016; Vafeiadi et al 2016; Zhang et al 2015). …”
Section: Introductionmentioning
confidence: 99%